2019
DOI: 10.1016/j.sbi.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Copper trafficking in eukaryotic systems: current knowledge from experimental and computational efforts

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…Consistent with these findings, K60 is well known as a critical residue for the interaction and stability of the complex [54], as well as for the transport mechanism of Cu(I) from Atox1 to MBD4. Moreover, we showed that the change in the protonation state of the metal-binding motif, known to affect transport [55], was most likely different in the presence of Cys-to-Ser mutations. This strikingly affected the structural, and possibly the functional, properties of the hosting proteins, which is consistent with the differences observed in CW-EPR spectra and the cross-linking experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these findings, K60 is well known as a critical residue for the interaction and stability of the complex [54], as well as for the transport mechanism of Cu(I) from Atox1 to MBD4. Moreover, we showed that the change in the protonation state of the metal-binding motif, known to affect transport [55], was most likely different in the presence of Cys-to-Ser mutations. This strikingly affected the structural, and possibly the functional, properties of the hosting proteins, which is consistent with the differences observed in CW-EPR spectra and the cross-linking experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, both the experimental and the simulation data consistently showed that Cu(I) can still bind to proteins after the Cys-to-Ser mutations. In addition, molecular simulations revealed that along the metal transport route mediated by Atox1-ATP7B the serine residues will most likely remain protonated, or if deprotonated, they would most likely easily sequester a proton from K60, a critically important residue for adduct stability, as indicated by mutagenesis studies [55]. This would either hamper the metal’s release from Atox1 to the target MBD4 protein or affect the stability of the Atox1-ATP7B adduct.…”
Section: Discussionmentioning
confidence: 99%
“…SLC31A1 is primarily expressed at the cell membrane and drives the uptake of copper from food in a potassium-dependent manner [478,480]. Copper homeostasis is critical for cells, as many enzymes are dependent on it for proper function [481].…”
Section: Slc30/slc39mentioning
confidence: 99%
“…Recently, we conducted electron paramagnetic resonance (EPR) spectroscopy experiments in order to better understand the interaction between the Atox1 metallochaperone and MBD3-4 as a function of Cu(I) binding [23,25]. The power of EPR spectroscopy lies in its ability to target conformational changes in solution, without limiting the protein size or the system.…”
Section: Introductionmentioning
confidence: 99%